Bioglass powder containing nano titanium nitride as well as preparation method and application of bioglass powder
By introducing nanotitanium nitride into bioglass and using near-infrared light regulation, the problem of the release of active ingredient in the middle and late stages of implantation of bioglass and the reduction of hydroxyapatite generation speed is solved, and the sustainable repair of bone tissue is achieved.
Patent Information
- Application Number
- CN202411686098.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-24
- Publication Date
- 2025-02-28
AI Technical Summary
In the middle and late stages of implantation, the release rate of active ingredient and the generation rate of hydroxyapatite in existing biological glasses are significantly reduced, resulting in a delay in bone repair.
Using nano-titanium nitride-containing bioglass powder, which contains 75-95% bioglass powder and 5-25% nano-titanium nitride powder, the degree of bonding between nano-titanium nitride particles and bioglass particles is changed by adjusting the melting temperature and time, the sustainable heating of bioglass in the liquid environment is achieved, and the release of active ingredients and the generation of hydroxyapatite is promoted through near-infrared light regulation.
It effectively promotes the release of active ingredients in bioglass and the generation of hydroxyapatite, maintains the biological activity of bioglass in the middle and late stages of implantation, and achieves sustainable repair of bone tissue.
Smart Images

Figure CN119528444A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomaterials and relates to a bioglass powder containing nano titanium nitride and a preparation method and application thereof. Background Art
[0002] Osteoporosis is a systemic bone disease characterized by low bone mass, damaged bone microstructure, increased bone brittleness, and susceptibility to fractures. Its serious consequence is osteoporotic fractures, which are more common in elderly patients. With the continuous increase in the proportion of the elderly population in my country, the number of fracture cases caused by osteoporosis has surged to more than one million each year, and traditional treatments such as reduction and fixation are often accompanied by high risks of postoperative infection, bleeding, and complications. Bioglass is a medical bone repair material with excellent biocompatibility and bioactivity. It can mineralize on the surface to form bone-like hydroxyapatite in the body, inducing bone growth and bone reconstruction; at the same time, the active ingredients released by bioglass degradation in the body can promote osteoblast proliferation, inhibit osteoclasts, and support soft tissue ingrowth, showing excellent bone repair properties.
[0003] Studies have reported that the active ingredient boron (B) has significant effects in promoting the proliferation of bone marrow mesenchymal stem cells, promoting osteogenesis and regulating bone metabolism balance [Skallevold HE, Rokaya D, Khurshid Z, et al. Bioactive glass applications in dentistry [J]. International Journal of Molecular Sciences, 2019, 20 (23): 1-24. Nasrollah S AS, Najmoddin N, Mohammadi M, et al. Three-dimensional polyurethane / hydroxyapatite bioactive scaffolds: The role of hydroxyapatite on pore generation [J]. Journal of Applied Polymer Science, 2021, 138 (11): 1-14.]; the active ingredient silicon (Si) can promote the osteogenic differentiation of bone marrow mesenchymal stem cells and stimulate osteoblast proliferation [Jones JR, Tsigkou O, Coates EE, et al. Extracellular matrix formation and mineralization on a phosphate-free porous bioactive glass scaffold using primary human osteoblast(HOB)cells[J].Biomaterials.2007,28:1653-63.Reffitt D,Ogston N,Jugdaohsingh R,et al.Orthosilicic acid stimulates collagen type 1synthesis and osteoblastic differentiation in human osteoblast-like cells invitro[J].Bone.2003,32:127-35.]; the active ingredient calcium (Ca) can provide raw materials for the formation and growth of bone-like hydroxyapatite[Maeno S,Niki Y,Matsumoto H,et al.The effect of calcium ionconcentration on osteoblast viability,proliferation and differentiation inmonolayer and 3D culture[J].Biomaterials.2005,26:4847-55.Bomi,Framroze,Freddy,etal.An in vitro study on the effect of five commercial calciumsupplements on human osteoblast cell proliferation and Ca. 2+ mineralization[J].Journal of Nutrition&Food Sciences,2017,8(6):1-5.].
[0004] However, the applicant of the present invention found that the release rate of active ingredients in bioglass and the generation rate of hydroxyapatite on the surface of bioglass were significantly reduced after 1 to 2 weeks of implantation. From the release behavior of active ingredients of bioglass in human body or simulated body fluid and the mechanism of hydroxyapatite generation, in the middle and late stages of implantation, the continuous generation and accumulation of hydroxyapatite on the surface of bioglass hindered the further release of active ingredients such as B, Si, and Ca in bioglass, which in turn led to the reduction of bioglass activity and delayed the bone repair process. Summary of the invention
[0005] Technical issues to be solved
[0006] In order to avoid the shortcomings of the prior art, the present invention proposes a nano-titanium nitride-containing bioglass powder and a preparation method and application thereof. The nano-titanium nitride-containing bioglass not only has a significant photothermal effect, but also can change the degree of bonding between nano-titanium nitride particles and bioglass particles by adjusting the melting temperature and time, thereby achieving sustainable heating of the bioglass in a liquid environment.
[0007] Technical Solution
[0008] A nano-titanium nitride-containing bioglass powder, characterized in that it contains 75-95% by mass of bioglass powder and 5-25% by mass of nano-titanium nitride powder; under the regulation of near-infrared light, the active ingredients in the bioglass powder are released and hydroxyapatite is generated on the surface of the bioglass powder.
[0009] The bioglass powder includes silicate, borate or borosilicate bioglass powder.
[0010] The particle size of the bioglass powder is 74-154 μm.
[0011] The particle size of the nano titanium nitride powder is 40-50nm.
[0012] A method for preparing nano-titanium nitride-containing bioglass powder is characterized by the following steps:
[0013] The bioglass powder and the nano-titanium nitride powder are mixed evenly according to a certain proportion to obtain a mixed powder of the bioglass powder and the nano-titanium nitride powder;
[0014] The mixed powder is placed in a muffle furnace and melted at a temperature of 650 to 800° C. for 10 to 15 minutes to obtain a bioglass block containing nano-titanium nitride;
[0015] The nano-titanium nitride-containing bioglass block is crushed to obtain the nano-titanium nitride-containing bioglass powder.
[0016] The melting is carried out in a step-by-step manner, with the first gradient being 650±10°C, 15±2min; the second gradient being 700±5°C, 10±1min; the third gradient being 750±5°C, 10±1min; and the fourth gradient being 800±5°C, 10±1min.
[0017] The bioglass powder and nano titanium nitride powder are mixed by grinding them separately and then mixing them.
[0018] When the nano-titanium nitride-containing bioglass block is crushed, a planetary ball mill is used; after ball milling, the nano-titanium nitride-containing bioglass powder is sieved to obtain the particle size of 74 to 154 μm.
[0019] An application method of the nano-titanium nitride-containing bioglass powder is characterized in that after the nano-titanium nitride-containing bioglass powder is regulated by near-infrared light, the active ingredients in the bioglass are released, inducing the formation of hydroxyapatite on the surface of the bioglass, and the bioglass powder is used in the field of bone repair and bone regeneration in bone tissue engineering.
[0020] The wavelength of the applied near infrared light is 808-1064 nm, and the power density is 1-2 W / cm 2 The application frequency is 0.5 to 2 hours / time and 1 to 4 times / day.
[0021] Beneficial Effects
[0022] The present invention proposes a nano-titanium nitride-containing bioglass powder and its preparation method and application. The bioglass contains the following components in mass percentage: 75-95% bioglass powder and 5-25% nano-titanium nitride powder; the melting process of the nano-titanium nitride-containing bioglass includes the following conditions: temperature 650-800°C, time 10-15min; the photothermal treatment method includes applying near-infrared light to the nano-titanium nitride-containing bioglass powder to regulate the release of active components in the bioglass, and can also include inducing the formation of hydroxyapatite on the surface of the bioglass. Compared with the prior art, in the present invention, the bioglass not only has a significant photothermal effect, but also in the experiment of simulating implantation in the human body environment, the nano-titanium nitride powder is not easy to be lost, and the photothermal performance of the nano-titanium nitride bioglass is maintained well; by applying near-infrared light to regulate the release of active components in the bioglass and the formation of hydroxyapatite on the surface of the bioglass, the controllable and sustainable repair of bone tissue is achieved. The technology can be applied to bone repair, regeneration and other fields in bone tissue engineering.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. Our research results show that the introduction of nano-titanium nitride into bioglass can give the bioglass excellent photothermal effect. Bioglass containing nano-titanium nitride has strong absorption in both near-infrared biological window I (750-1000nm) and near-infrared biological window II (1000-1350nm), among which the photothermal conversion efficiency in near-infrared biological window II is higher.
[0025] 2. Our research results show that after applying near-infrared light, the temperature generated by nano-titanium nitride is almost completely transferred to the bioglass, and the ambient temperature around the material is always at a low temperature (normal human body temperature is 37°C). As long as the application time of near-infrared light is not too long, the temperature rise caused by the photothermal effect will not cause irreversible damage to the environment, tissues, cells, etc. around the material.
[0026] 3. Our research results show that after the nano-titanium nitride bioglass powder was immersed in human simulated body fluid for 12 days, the application of near-infrared light can effectively promote the release of active ingredients such as B, Si and Ca in the bioglass, maintain the biological activity of the bioglass in the middle and late stages of implantation, and achieve sustainable repair of bone tissue.
[0027] 4. Our research results show that applying near-infrared light can effectively regulate the formation and growth of hydroxyapatite on the surface of bioglass and promote bone repair.
[0028] 5. The bone repair performance of bioglass can be regulated by changing the amount of nano-titanium nitride introduced and the application conditions of external near-infrared light (wavelength, power density, application frequency, etc.), so as to meet the repair needs after bone surgery in different parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a high-resolution transmission electron microscope (HR-TEM) photograph of the nano-titanium nitride bioglass prepared in Example 3 of the present invention; wherein, Figure 1 (a) is a HR-TEM image of the nano-titanium nitride bioglass after heat treatment in a muffle furnace at 750°C for 10 min. Figure 1 (b) is the electron diffraction pattern of (a). Figure 1 In (a), it can be clearly seen that granular materials are scattered in the amorphous glass structure network. Figure 1 (b) Electron diffraction confirmed that the granular material was nano-titanium nitride.
[0030] Figure 2 A schematic diagram of a device in which nano-titanium nitride-containing bioglass is immersed in human simulated body fluid and near-infrared light is applied;
[0031] Figure 3 The nano-titanium nitride bioglass prepared in Example 1, Example 2, Example 3 and Example 4 of the present invention is subjected to near-infrared light (wavelength of 1064nm, power density of 1W / cm 2 The temperature rise curve after melting indicates that the bioglass containing nano-titanium nitride has a good photothermal effect, and its photothermal performance can be regulated by changing the melting conditions.
[0032] Figure 4 After the nano-titanium nitride-containing bioglass prepared in Example 3 of the present invention was immersed in human simulated body fluid at 37°C for 11 days, most of the active ingredients in the bioglass had been released. At the same time, the Si-OH layer and Ca-P compounds generated on the surface of the glass further hindered the release of active ingredients in the bioglass. At this point, the release of active ingredients in the bioglass reached a bottleneck. In this case, near-infrared light was applied to the nano-titanium nitride-containing bioglass, and the released concentrations of B, Si, and Ca in the bioglass were detected on the 12th day. The results are as follows: Figure 4 As shown. Since nano-titanium nitride adheres to the surface of bioglass, it hinders the direct contact between bioglass and human simulated body fluids. Therefore, the active ingredient release concentration of bioglass containing nano-titanium nitride without near-infrared light is lower than that of bioglass. However, the active ingredient release concentration of bioglass containing nano-titanium nitride with near-infrared light is significantly higher than that of the other two groups. This shows that the application of near-infrared light can effectively promote the release of active ingredients of bioglass containing nano-titanium nitride in the middle and late stages of implantation.
[0033] Figure 5X-ray diffraction pattern of the nano-titanium nitride-containing bioglass prepared in Example 3 of the present invention after being immersed in human simulated body fluid at 37°C for 14 days. Among them, the black curve is the X-ray diffraction pattern of the bioglass, the blue curve is the X-ray diffraction pattern of the nano-titanium nitride-containing bioglass, and the red curve is the X-ray diffraction pattern of the nano-titanium nitride-containing bioglass applied with near-infrared light (2h / time, 4 times / d). It shows that the application of near-infrared light can effectively promote the formation of hydroxyapatite on the surface of the nano-titanium nitride-containing bioglass. DETAILED DESCRIPTION
[0034] The present invention will now be further described with reference to the embodiments and the accompanying drawings:
[0035] The purpose of the present invention can be achieved by the following technical solutions:
[0036] In one aspect, the present invention provides a nano-titanium nitride-containing bioglass, comprising the following components in percentage by mass:
[0037] Bioglass powder 75~95%,
[0038] Nano titanium nitride powder 5-25%.
[0039] Preferably, the bioglass powder comprises silicate, borate or borosilicate bioglass powder.
[0040] Preferably, the particle size of the bioglass powder is 74-154 μm.
[0041] Preferably, the particle size of the nano titanium nitride powder is 40 to 50 nm.
[0042] The second aspect of the present invention provides a method for preparing the nano-titanium nitride-containing bioglass, comprising the following melting process:
[0043] (1) mixing the bioglass powder and the nano-titanium nitride powder evenly to obtain a mixed powder of the bioglass powder and the nano-titanium nitride powder;
[0044] (2) placing the mixed powder in a muffle furnace and melting it at a temperature of 650 to 800° C. for 10 to 15 minutes to obtain a bioglass block containing nano-titanium nitride;
[0045] (3) crushing the nano-titanium nitride-containing bioglass block in a planetary ball mill to obtain nano-titanium nitride-containing bioglass powder.
[0046] Preferably, in step (1), the mixing is performed by grinding. More preferably, in step (1), the mixing is performed by grinding at room temperature for about 1 minute.
[0047] Preferably, in step (2), the melting conditions are 650°C-15 min, 700°C-10 min, 750°C-10 min and 800°C-10 min respectively.
[0048] Preferably, the nano-titanium nitride-containing bioglass powder obtained in step (3) is sieved to obtain nano-titanium nitride-containing bioglass powder with a particle size of 74 to 154 μm.
[0049] The third aspect of the present invention also provides the near-infrared light treatment method of the nano-titanium nitride-containing bioglass, which applies near-infrared light to the nano-titanium nitride-containing bioglass powder.
[0050] Preferably, near-infrared light is applied to the nano-titanium nitride-containing bioglass powder to regulate the release rate of active ingredients in the bioglass and the generation rate of hydroxyapatite on the surface of the bioglass.
[0051] Preferably, the nano-titanium nitride-containing bioglass powder is placed in human simulated body fluid and near-infrared light is applied.
[0052] Preferably, the near infrared light wavelength is 808-1064 nm, and the power density is 1-2 W / cm 2 The application frequency is 0.5 to 2 hours / time and 1 to 4 times / day.
[0053] Example 1
[0054] (1) Preparation of mixed powder of bioglass powder and nano titanium nitride powder
[0055] 0.75 g of bioglass powder (particle size 74-154 μm) prepared by high-temperature melting method and 0.25 g of nano-titanium nitride powder (particle size 40-50 nm) were placed in an agate mortar and ground and mixed at room temperature for about 1 min to obtain a mixed powder of bioglass powder and nano-titanium nitride powder.
[0056] (2) Preparation of nano-titanium nitride-containing bioglass powder
[0057] A mixed powder of 1g of bioglass powder and nano-titanium nitride powder is placed in a 5ml corundum crucible and covered with a corundum crucible lid, then placed in a muffle furnace and melted at 650°C for 15 minutes to obtain a bioglass block containing nano-titanium nitride. After natural cooling at room temperature, it is crushed and sieved to obtain a bioglass powder containing nano-titanium nitride with a particle size of 74 to 154μm.
[0058] Example 2
[0059] This embodiment is substantially the same as embodiment 1, except that, in this embodiment, the melting condition is heat treatment at 700° C. for 10 min.
[0060] Example 3
[0061] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the melting condition is heat treatment at 750° C. for 10 minutes.
[0062] Figure 1 The high-resolution transmission electron microscope (HR-TEM) photo of the nano-titanium nitride bioglass prepared in Example 3 is shown. Figure 1 (a) is a HR-TEM image of the nano-titanium nitride bioglass after heat treatment in a muffle furnace at 750°C for 10 min. Figure 1 (b) is the electron diffraction pattern of (a). Figure 1 In (a), it can be clearly seen that granular materials are scattered in the amorphous glass structure network. Figure 1 (b) Electron diffraction confirmed that the granular material was nano-titanium nitride.
[0063] Figure 4 The nano-titanium nitride bioglass prepared in Example 3 has released most of the active ingredients after being immersed in human simulated body fluid at 37°C for 11 days. At the same time, the Si-OH layer and Ca-P compounds generated on the surface of the glass further hinder the release of active ingredients in the bioglass. At this point, the release of active ingredients in the bioglass reaches a bottleneck. In this case, near-infrared light is applied to the nano-titanium nitride bioglass, and the release concentrations of B, Si, and Ca in the bioglass are detected on the 12th day. The results are as follows: Figure 4 As shown. Since nano-titanium nitride adheres to the surface of bioglass, it hinders the direct contact between bioglass and human simulated body fluids. Therefore, the active ingredient release concentration of bioglass containing nano-titanium nitride without near-infrared light is lower than that of bioglass. However, the active ingredient release concentration of bioglass containing nano-titanium nitride with near-infrared light is significantly higher than that of the other two groups. This shows that the application of near-infrared light can effectively promote the release of active ingredients of bioglass containing nano-titanium nitride in the middle and late stages of implantation.
[0064] Figure 5 The X-ray diffraction diagram of the nano-titanium nitride-containing bioglass prepared in Example 3 after being immersed in human simulated body fluid at 37°C for 14 days is shown. Among them, the black curve is the X-ray diffraction diagram of the bioglass, the blue curve is the X-ray diffraction diagram of the nano-titanium nitride-containing bioglass, and the red curve is the X-ray diffraction diagram of the nano-titanium nitride-containing bioglass applied with near-infrared light (2h / time, 4 times / day). It shows that the application of near-infrared light can effectively promote the formation of hydroxyapatite on the surface of the nano-titanium nitride-containing bioglass.
[0065] Example 4
[0066] This embodiment is substantially the same as embodiment 1, except that, in this embodiment, the melting condition is heat treatment at 800° C. for 10 min.
[0067] Figure 3 The nano-titanium nitride bioglass prepared in Example 1, Example 2, Example 3 and Example 4 can be used to generate nano-titanium nitride bioglass under near-infrared light (wavelength of 1064 nm, power density of 1 W / cm 2 The temperature rise curve after melting indicates that the bioglass containing nano-titanium nitride has a good photothermal effect, and its photothermal performance can be regulated by changing the melting conditions.
[0068] Example 5
[0069] The nano-titanium nitride bioglass powder (1 g) was immersed in 37°C human simulated body fluid (10 ml), and then irradiated with near-infrared light (wavelength 1064 nm, power density 1 W / cm 2 ). The photothermal properties of the samples were characterized using a thermometer. The results are as follows Figure 3 The temperature rise of the bioglass containing nano-titanium nitride is 2 to 3 times that of the bioglass, indicating that the bioglass containing nano-titanium nitride has good photothermal properties.
[0070] Example 6
[0071] After immersing the nano-titanium nitride bioglass powder (1g) in 37°C simulated human body fluid (10ml) for 11 days, the bioglass has released most of the active ingredients. At the same time, the Si-OH layer and Ca-P compounds generated on the surface of the glass further hinder the release of active ingredients in the bioglass. At this time, the release of active ingredients in the bioglass reaches a bottleneck. In this case, near-infrared light (wavelength of 1064nm, power density of 1W / cm 2 , radiation frequency is 2h / time, 4 times / day), and the release concentrations of B, Si, and Ca in the bioglass were detected on the 12th day. The results are as follows Figure 4 As shown in the figure, the concentration of active ingredients released by the nano-titanium nitride bioglass applied with near-infrared light was significantly higher than that of the other two groups. This indicates that the application of near-infrared light can effectively promote the release of active ingredients of nano-titanium nitride bioglass in the middle and late stages of implantation.
[0072] Example 7
[0073] The nano-titanium nitride bioglass powder (1 g) was immersed in 37°C human simulated body fluid (10 ml), and then near-infrared light (wavelength 1064 nm, power density 1 W / cm 2 , radiation frequency is 2h / time, 4 times / d). After 14 days, the X-ray diffraction results of the sample are as follows Figure 5As shown. After applying periodic near-infrared light, the diffraction peak of hydroxyapatite appeared in the spectrum of nano-titanium nitride bioglass, while the diffraction peak of hydroxyapatite did not appear in the spectrum of nano-titanium nitride bioglass and the spectrum of bioglass without infrared light. This result shows that the application of near-infrared light can effectively promote the formation of hydroxyapatite on the surface of nano-titanium nitride bioglass.
[0074] On this basis, in the embodiment, body fluids simulated by the human body are selected, and near-infrared light is applied to specifically increase the temperature of the bioglass, the release of active ingredients in the bioglass and the generation of hydroxyapatite.
[0075] It can be seen that by implanting nano-titanium nitride bioglass powder into the parts of the human body that need bone tissue repair, and then applying near-infrared light to specifically increase the temperature of the bioglass, the release of active ingredients in the bioglass and the formation of hydroxyapatite in the middle and late stages of implantation are promoted, thereby achieving sustainable repair of bone tissue.
Claims
1. A bioglass powder containing nano titanium nitride, characterized in that The bioglass powder contains 75-95% by mass and 5-25% by mass of nano titanium nitride powder. Under the regulation of near-infrared light, the active ingredients in the bioglass powder containing nano titanium nitride are released and hydroxyapatite is generated on the surface of the bioglass powder.
2. The nano-titanium nitride-containing bioglass powder according to claim 1, characterized in that: The bioglass powder includes silicate, borate or borosilicate bioglass powder.
3. The nano-titanium nitride-containing bioglass powder according to claim 1, characterized in that: The particle size of the bioglass powder is 74-154 μm.
4. The nano-titanium nitride-containing bioglass powder according to claim 1, characterized in that: The particle size of the nano titanium nitride powder is 40-50nm.
5. A method for preparing the nano-titanium nitride-containing bioglass powder according to any one of claims 1 to 4, characterized in that Here are the steps: The bioglass powder and the nano-titanium nitride powder are mixed evenly according to a certain proportion to obtain a mixed powder of the bioglass powder and the nano-titanium nitride powder; The mixed powder is placed in a muffle furnace and melted at a temperature of 650 to 800° C. for 10 to 15 minutes to obtain a bioglass block containing nano-titanium nitride; The nano-titanium nitride-containing bioglass block is crushed to obtain the nano-titanium nitride-containing bioglass powder.
6. The method according to claim 5, characterized in that: The melting is carried out in a step-by-step manner, with the first gradient being 650±10°C, 15±2min; the second gradient being 700±5°C, 10±1min; the third gradient being 750±5°C, 10±1min; and the fourth gradient being 800±5°C, 10±1min.
7. The method according to claim 5, characterized in that: The bioglass powder and nano titanium nitride powder are mixed by grinding them separately and then mixing them.
8. The method according to claim 5, characterized in that: When the nano-titanium nitride-containing bioglass block is crushed, a planetary ball mill is used; after ball milling, the nano-titanium nitride-containing bioglass powder is sieved to obtain the particle size of 74 to 154 μm.
9. A method for using the nano-titanium nitride-containing bioglass powder according to any one of claims 1 to 4, characterized in that: After the nano-titanium nitride bioglass powder is subjected to near-infrared light regulation, the active ingredients in the bioglass are released, inducing the formation of hydroxyapatite on the surface of the bioglass, which is used in the fields of bone repair and bone regeneration in bone tissue engineering.
10. The application method according to claim 9, characterized in that: The wavelength of the applied near infrared light is 808-1064 nm, and the power density is 1-2 W / cm 2 The application frequency is 0.5 to 2 hours / time and 1 to 4 times / day.